Determinants of Corporate Environmental Accounting Disclosure of Oil and Gas Firms in Nigeria (Global Business Management Review (GBMR), 2021)
This study examines the cognitive factors that determine corporate environmental accountingdisclosures (CEAD). The population consists of all the fourteen (14) listed oil and gas firms in Nigeria.Panel data were obtained from the annual reports and accounts of the firms for the period of 2010 to2019. A correlational research design was used and the data were analyzed using the Generalized LeastSquare regression (random model). The study found that firm size; leverage and multi-nationalcompanies have positive significant influence on the CEAD of listed oil and gas firms in Nigeria. Whilstfirm growth has a negative significant relationship with the CEAD of listed oil and gas firms in Nigeria.It is concluded that larger firms and multi-national companies in the Nigerian oil and gas sector havehigh likelihood of disclosing environmental accounting information. Thus, it is recommended that themanagement of listed oil and gas firms in Nigeria should expand their size by acquiring more assets,maintain a consistent growth by exploring more opportunities while improving their gearing ratio toensure a stable balance between the proportion of debt and assets. It therefore, highlighted the need forSecurities and Exchange Commission (SEC) to come up with enabling laws geared towards ensuringthat listed oil and gas firms in Nigeria embrace CEAD. Furthermore, Global Environmental DisclosureIndex (GEI) should be considered as the most acceptable yardstick for measuring environmentalaccounting by the listed oil and gas firms in Nigeria.